Restoring Segmental Biomechanics Through Nucleus Augmentation: An In Vitro Study. Issue 10 (December 2016) - Pelletier, Matthew H.; Cohen, Charles S.; Ducheyne, Paul; Walsh, William R.
Abstract : Study Design: In vitro biomechanical laboratory study. Objectives: The purpose of this study is to evaluate a mechanical treatment to create a degenerative motion segment and the ability of nucleus augmentation to restore biomechanics. Summary of Background: In cases with an intact annulus fibrosus, the replacement or augmentation of the nucleus pulposus alone may provide a less invasive option to restore normal biomechanics and disk height when compared with spinal fusion or total disk replacement. Laboratory testing allows these changes to be fully characterized. However, without preexisting pathology, nucleus augmentation therapies are difficult to evaluate in vitro. Methods: The present study evaluated pure moment bending and compressive biomechanics in 3 states (n=6): (1) intact, (2) after creep loading and nucleus disruption to induce degenerative biomechanical changes, and (3) after nucleus augmentation through an injectable polymer (DiscCell). Results: Neutral zone and ROM were increased in all modes of bending after the degenerative treatment. The most sensitive mode of bending was lateral bending, with intact ROM (20.0±2.9 degrees) increased to 22.3±2.6 degrees after degenerative treatment and reduced to 18.4±1.6 degrees after injection of the polymer. All bending ROM and NZ changes induced by the degenerative treatment were reversed by nucleus augmentation. Conclusions: This material was shown to be effective at altering motion segment biomechanics and restoring disk height during time zero tests. This technique may provide a model to examine the time zero performance of a nucleus augmentation device/material.